Intrathecal Dexmedetomidine 5 µg Prolongs Post-Spinal Analgesia in Elective Lower-Limb Orthopaedic Surgery: A Prospective, Randomised, Double-Blind Trial - Dr. Arvind Patel; Dr. Rashmi Kumari; Dr. Deepesh (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Prolonging spinal-anaesthetic analgesia without raising complication rates remains a central goal in orthopaedic anaesthesia. Α-2-agonist dexmedetomidine (DEX) is increasingly injected intrathecally as an adjuvant, yet evidence in lower-limb orthopaedic surgery is heterogeneous. Methods: In this prospective, double-blind, parallel-arm trial, 60 adults (ASA I–II) scheduled for elective lower-limb fixation under spinal anaesthesia were randomised to hyperbaric bupivacaine 0.5 % 3.5 mL plus 0.5 mL saline (Control) or plus DEX 5 µg (DEX group). Primary end-point was duration of effective analgesia (time from intrathecal injection to first rescue analgesic). Secondary outcomes included onset times, block characteristics, haemodynamics, adverse events and 24 h opioid-sparing. Results: All patients completed follow-up. Mean analgesia duration increased from 258 ± 44 min to 327 ± 41 min (∆ ≈ 69 min, P < 0.001). Sensory onset was faster (3.1 ± 0.5 vs 3.8 ± 0.6 min, P = 0.002) and two-segment regression slower (212 ± 35 vs 153 ± 38 min, P < 0.001) with DEX. Post-operative morphine equivalents fell by 38 %. Haemodynamic profiles were comparable, although bradycardia occurred more often with DEX (5 vs 1 patients, NS). No neuro-toxic events were observed. Conclusion: A single 5-µg dose of intrathecal dexmedetomidine significantly and safely prolongs analgesia after lower-limb orthopaedic surgery, reduces rescue-opioid need and accelerates block onset without increasing major adverse effects. The findings support routine use of low-dose DEX as an effective spinal adjuvant in lower-extremity trauma and reconstructive procedures.